Zirconium in the Nuclear Industry: 15th International Symposium 2009
DOI: 10.1520/stp48141s
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Structure and Chemistry in Zircaloy-2 and the Resulting Oxide After High Temperature Corrosion

Abstract: A plate of Zircaloy-2 received in the β-quenched condition was heat treated to vary systematically the size of the second phase particles (SPPs) and the content of alloying elements retained in solid solution. Scanning electron microscopy and thermoelectric power measurements were used to quantify these microstructural parameters. Specimens were exposed for different periods of time in autoclaves at 415°C and at 500°C in steam, and corrosion was assessed according to the gain in weight. Effects of the microstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Whereas the usual approximation made is that all the oxygen ingress results in the formation of ZrO 2 , this is not strictly true: the region ahead of the advancing oxide front has been reported to show a complex microstructure with a variety of oxide phases exhibiting lower oxygen content than 66 at.% [13][14][15][16]. Particularly studies of the oxide-metal interface demonstrated by both electron energy loss spectroscopy (EELS) and atom probe tomography (APT) that one of the lower stoichiometry oxide phases is equiatomic suboxide ZrO [17][18][19][20], which is only present in pre-transition alloys and disappears after transition [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the usual approximation made is that all the oxygen ingress results in the formation of ZrO 2 , this is not strictly true: the region ahead of the advancing oxide front has been reported to show a complex microstructure with a variety of oxide phases exhibiting lower oxygen content than 66 at.% [13][14][15][16]. Particularly studies of the oxide-metal interface demonstrated by both electron energy loss spectroscopy (EELS) and atom probe tomography (APT) that one of the lower stoichiometry oxide phases is equiatomic suboxide ZrO [17][18][19][20], which is only present in pre-transition alloys and disappears after transition [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is known that the initial oxide does not generally consist of stoichiometric ZrO 2 but is in fact a sub-oxide having the approximate composition of ZrO [6][7][8]. For Zircaloy materials oxidised in autoclaves, as in the present case, the thickness of the sub-oxide layer is in the range 200-300 nm.…”
Section: Discussionmentioning
confidence: 73%
“…3. This was the same material as described in a previous publication where more details were provided [8].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations